(untitled) (Italian Journal of Public Health, 2009)
Background: Most of the world’s vaccines are produced in Europe. Although vaccine licensure can be centralized through the EMEA, immunization recommendations are established at the national levels, reimbursement policies vary widely (ranging from regional to national, from private to public) and the lag time can be long between licensure and eventual introduction into a national immunization program. Methods: An example of this discordance is the paediatric combination vaccines. Young infants in some EU countries receive a whole-cell pertussis vaccine, in a three- to five-vaccine combination (“DTPw | IPV | Hib”). Acellular pertussis vaccines have been introduced over the last decade in many other EU countries, with four- to six-vaccine combinations (“DTPa | IPV | HBV | Hib”). Either of these combinations may be administered with a “3 + 1” schedule, with the first dose given between the age of 2 to 3 months, a spacing of 1 to 2 months between doses, and the final (booster) dose usually given at anywhere between 12 and 24 months of age, but in a handful of countries as late as the age of 3 to 5 years. By contrast, a “2 + 1” schedule is applied in some countries for the “DTPa | IPV | Hib” or “DTPa | IPV | HBV | Hib” vaccines: first dose, 3 months old; spacing, 2 months between doses; final (booster) dose, 11 to 14 months of age. Results: Differing national policies in the EU may have led to delays in the introduction of the newest vaccines (e.g., pneumococcal conjugate, meningococcal conjugate, rotavirus, influenza, varicella-zoster, etc.) that must be shown to be compatible with the various infant immunization programs across Europe. This could delay the likelihood, in some EU countries, of the public health advancements that these new vaccines can provide. Conclusions: Sharing of best practices from vaccination schedules might rationalize vaccine development, streamline the introduction of novel vaccines into the national immunization programs, and facilitate the evaluation of the impact of new vaccines in Europe.